Research on Microstructure and Growth Mechanism of Different Primary Silicon in Hypereutectic Aluminum Alloy. Issue 1 (January 2022) - Zhao, Gaozhan; Xing, Zhihui; Li, Ming; Gao, Shiqing; Tao, Jianquan; Chai, Shuxin
Abstract: The as-cast microstructure of a typical hypereutectic Al-25Si alloy was studied, and the growth mechanism of different primary silicon phases was analyzed. The results show that the as-cast microstructure phase composition of the alloy is mainly primary silicon and eutectic silicon. Primary silicon is mainly petal-like, massive and other complex polyhedrons, and there are a lot of cavities, cracks and other defects in the interior and boundary; Eutectic silicon is coarse and long needle-like, and the distribution is relatively messy, which seriously deteriorates the mechanical properties and cutting performance, and hinders the further application of the alloy in the field of lightweight pistons. Petal-shaped primary silicon is grown by combining five tetrahedral crystal nuclei in the melt into a decahedron, while bulk primary silicon is mainly caused by the unbalanced aggregation of impurity elements. And these two types of silicon phase growth methods are related to the twin groove growth mechanism, which is the result of a combination of multiple mechanisms.